The Role of Cooperative Societies in Seed Distribution: A Case Study of Punjab, India - Sidhu, Jashleen Kaur; Rampal, Vipan Kumar (Indian Journal of Extension Education, 2024)
Cooperative societies, integral to the formal seed system, are crucial for agricultural development, providing resources, inputs etc. The study was conducted in 2023 and aimed to analyze the role of cooperative societies in distributing wheat and rice seeds to farmers, examine farmer satisfaction levels, and identify problems faced by them in seed procurement. Using a multi-stage sampling design, the study was conducted in Punjab across five agro-climatic zones. One district with the highest wheat and rice production was selected from each zone, followed by random selection of one block per district, two villages per block, and 20 farmers per village, making a total sample of 200 farmers. Village cooperative society secretaries were also interviewed. Results indicated 60 per cent of farmers were cooperative society members, but only 8.5 per cent procured wheat seed from these societies. In 2022, 11.76 per cent of members procured wheat seed, rising to 17.65 per cent in 2023. Most farmers reported high satisfaction with seed quality and quantity, and all found prices affordable. Major issues included late seed arrival and lack of information regarding availability. The majority preferred procuring seeds from cooperative societies in the future. It is recommended to improve financial management and enhance logistics to ensure timely seed availability.
Keywords: Cooperative society; Seed distribution; Satisfaction level; Problems; Future preferences